Electrochemical Study of Selenocystine Reactivity and Reduction at Metallic Surfaces. Issue 5 (4th May 2017) - Karnaukh, Elizabeth A.; Walker, Lindsey M.; Lynch, Kelsey A.; Wiita, Elizabeth G.; Buzzeo, Marisa C.
Abstract: The reduction of seleno‐L‐cystine is examined on gold and platinum electrodes in aqueous solution. The voltammetric behavior is indicative of a two‐step process, in which the metallic substrate is modified by the diselenide analyte prior to observation of diffusionally controlled, proton‐coupled electron transfer. X‐ray photoelectron spectroscopy confirms the presence of selenium on gold foil samples that have been reductively cycled in selenocystine solution. The selenium‐based surface modification, which is accessible through multiple preparation routes, can be removed by anodic stripping and fully restored through subsequent cycling. The described electrochemical approach allows for the analysis of redox‐active chalcogen‐containing species under physiologically relevant conditions. Abstract : Cycling in selenium : The voltammetric profile of seleno‐L‐cystine at gold and platinum electrodes is examined. Electrode pre‐treatment by reductive cycling yields a selenium adsorbate layer and makes accessible quasi‐reversible diffusional behavior that is consistent with a two‐proton, two‐electron process. The surface modification can be electrochemically removed and regenerated with high reproducibility.